(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Storks were studied by directly observing them in the Maya(meadow) ecosystem of Dinder National Park (DNP) during the dryseasons of 2009 and 2010. The objective was to determine their diversity,flock characteristics, roosting ecology and the annual fluctuation in theirnumbers. The numbers were ascertained by the double samplingprocedure in which the number of each stork species in a flock wasestimated and was then directly counted. A predictive model wasdeveloped from the relationship between the counted and the estimatedvariables. Subsequently, the number was only estimated and the actualcount was predicted from the regression model. The tree density wasdetermined by the nearest neighbour method. The crown diameters of thetrees were measured, and the crown areas were calculated. Eight speciesof storks; namely, the black (Ciconia nigra), the white (Ciconia ciconia),the Abdim’s (Ciconia abdimii), the yellow-billed (Mycteria ibis), theAfrican open bill (Anastomus lamelligerus), the woolly-necked (Ciconiaepiscopus), the marabou (Leptoptilos crumeniferus) and the saddle bill(Ephippiorhynchus senegalensis), occurred in DNP. The black and thewhite storks are Palearctic migrants, whereas the Abdim’s, the woolly-necked, the African open bill and the yellow-billed are local migrants; themarabou and the saddle bill are resident. The three species that occurredin large flocks were the yellow-billed, the marabou and the open bill. Thetotal number of storks in 2010 was lower than that in 2009. This declinewas attributed to severe drought that struck the DNP in 2010.